2020
DOI: 10.2147/rmhp.s247356
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychometric Properties of a Questionnaire on Brucellosis Prevention Behaviors Based on the PRECEDE Model Among Rural Farmers and Their Family Members</p>

Abstract: Introduction: Brucellosis is one of the most prevalent diseases in Torbate Heidarieh, Iran; it is a common disease between human and animals. The present study aimed to review the psychometric properties of a questionnaire on brucellosis prevention behaviors based on the PRECEDE model among rural farmers and their family members (PRECEDE-QBPB). Materials and Methods:The study was a combination of qualitative and quantitative stages. In the qualitative stage, an 86-item questionnaire including interviews with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…Comparison of self with others, referred to as social comparison, is among the factors that can increase or decrease participants’ motivation to perform stress coping behaviors [ 13 ]. This finding is consistent with the results of studies conducted by Alizadeh-Siuki et al [ 23 ], Ghasemi et al [ 24 ] Nazari et al [ 25 ] and Nahidi et al [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Comparison of self with others, referred to as social comparison, is among the factors that can increase or decrease participants’ motivation to perform stress coping behaviors [ 13 ]. This finding is consistent with the results of studies conducted by Alizadeh-Siuki et al [ 23 ], Ghasemi et al [ 24 ] Nazari et al [ 25 ] and Nahidi et al [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Alizadeh-Siuki et al [ 23 ] examined the psychometric properties of a questionnaire on brucellosis prevention behaviors based on the PRECEDE model among rural farmers and their family members. In their study a questionnaire with 36 items and 8 subscales including knowledge, attitude, self-efficacy, social support, enabling factors, environmental factors, behavioral factors and reinforcing factors developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study recommended educational campaigns targeting shepherds. In contrast, a study done in rural Iran identified behavioral (such as boiling of raw milk and vaccination against brucellosis) and non-behavioral (such as age and educational level) factors influencing brucellosis prevention ( 16 ). The study underscored the importance of these factors in health education and promotion programs to address brucellosis effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nilai tersebut menjelaskan bahwa setiap butir pernyataan yang telah dikembangkan telah dinyatakan valid secara konten dan dapat digunakan. Hal ini sejalan dengan penelitian sebelumnya tentang pengembangan suatu instrumen yang menyatakan bahwa validitas konten (melalui perhitungan CVR) sangat penting dan krusial (Alizadeh-Siuki et al, 2020;Waltz et al, 2016).…”
Section: Hasil Dan Pembahasanunclassified